Assessing Pre-Service Teachers’ Analytical Thinking in Science Fundamentals through a Moodle-Based Online Test - Yusro, Andista Candra; Setyosari, Punaji; Degeng, I Nyoman Sudana; Degeng, Made Duananda Kartika (Journal of Educational Technology and Learning Creativity, 2025)
Purpose of the study: This study aims to assess the analytical thinking skills of second-year pre-service teachers in the Concepts of Science course using a Moodle-based online assessment, emphasizing higher-order cognitive skills in Bloom’s taxonomy. Methodology: A descriptive quantitative design was employed involving 58 students from the Primary School Teacher Education (PGSD) program. Data were collected through a Moodle-based online test consisting of 20 items measuring analytical thinking at the analyzing level (C4), focusing on differentiating, organizing, and attributing in fundamental science topics. Descriptive statistics were used to analyze students’ performance levels. Main Findings: The findings show that approximately 62% of students achieved a moderate level of analytical thinking. Students performed better in identifying relationships between variables and interpreting experimental results, while difficulties were observed in organizing and evaluating scientific information. This indicates that Moodle-based assessments are effective in measuring analytical thinking but require instructional reinforcement to strengthen higher-order cognitive processes.. Novelty/Originality of this study: This study provides empirical evidence on the effectiveness of Moodle-based assessments in evaluating analytical thinking skills aligned with Bloom’s taxonomy in science teacher education. It highlights the potential of digital assessment platforms to support valid, efficient, and scalable measurement of pre-service teachers’ analytical competencies.